Training, skill-upgrading and settlement intention of migrants: Evidence from China. (October 2019) - Wang, Qing; Ren, Ting; Liu, Ti
The massive rural-to-urban migration has been one of the most important features of China's labour market in recent decades. The recent pattern of return migration and migrant wages has increased the costs of firms in urban areas and has negatively affected urbanisation. Therefore, it is important to understand the determinants of settlement intention of migrants. Using data from Rural Urban Migration in China (RUMiC), we find that migrants express higher settlement intention in a city after receiving training that is provided by firms. The effect is larger for females, high school graduates and dropouts, and wage earners. These findings suggest that training may complement migrants' human capital and upgrade their skills. Therefore, training in cities may act as an instrument that facilitates the migration decisions and transforms a temporary migrant to a permanent resident in an urban area.